2017
DOI: 10.1021/acs.orglett.6b03601
|View full text |Cite
|
Sign up to set email alerts
|

Transition-Metal-Free Lactonization of sp2 C–H Bonds with CO2

Abstract: The transition-metal-free lactonization of heteroaryl and alkenyl C-H bonds with carbon dioxide is reported to synthesize important coumarin derivatives in moderate to excellent yields. These redox-neutral reactions feature a broad substrate scope, good functional group tolerance, facile scalability, and easy product derivatization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…11 Pyrazolofluostatin A 15, a metabolite of marine-derived Micromonospora rosaria, contains an unusal pyrazole ring. 12 The structures of both sophaline A 14 and pyrazolofluostatin A 15 were confirmed by X-ray analyses.…”
mentioning
confidence: 83%
“…11 Pyrazolofluostatin A 15, a metabolite of marine-derived Micromonospora rosaria, contains an unusal pyrazole ring. 12 The structures of both sophaline A 14 and pyrazolofluostatin A 15 were confirmed by X-ray analyses.…”
mentioning
confidence: 83%
“…Recently, lactonization by direct cyclocarbonylation or cyclocarboxylation has been demonstrated to be a powerful strategy for constructing the pyrone moiety of coumarins [ 70 , 71 ]. Cyclocarbonylation of 2-vinylphenol using a transition-metal catalyst is an atom-economical and environmentally attractive method for 4-arylcoumarin synthesis.…”
Section: Cyclocarbonylation and Cyclocarboxylation Toward Central mentioning
confidence: 99%
“…In 2017, Zhi et al reported a transition-metal-free and redox neutral lactonization by cyclocarboxylation of 2-alkenylphenol 46 to afford 4-arylcoumarin 47 [ 71 ] ( Scheme 9 ). They stated that the yield varies depending on the para substituent on the phenol ring.…”
Section: Cyclocarbonylation and Cyclocarboxylation Toward Central mentioning
confidence: 99%
“…A large body of evidence suggests that only "fixed CO2" (absorbed or adsorbed) by the solid reagent is involved in the carboxylation reaction, therefore 2,4,6-trimethylphenoxide may increase the amount of CO2 able to react being inert towards ortho-carboxylation itself (Scheme 64). Very recently Zhi reported a transition-metal-free carboxylation of C(sp 2 )-H bond with CO2 followed by a lactonization reaction applied to 2-(imidazo[1,2-a]pyridine-2-yl)phenol (154, Scheme 65) and 2-(1-arylvinyl)phenol derivatives (82, Scheme 66) [144]. Very recently Zhi reported a transition-metal-free carboxylation of C(sp 2 )-H bond with CO 2 followed by a lactonization reaction applied to 2-(imidazo[1,2-a]pyridine-2-yl)phenol (154, Scheme 65) and 2-(1-arylvinyl)phenol derivatives (82, Scheme 66) [144].…”
Section: Base-promoted Carboxylation Of Aromatic and Heteroaromatic Cmentioning
confidence: 99%
“…Very recently Zhi reported a transition-metal-free carboxylation of C(sp 2 )-H bond with CO2 followed by a lactonization reaction applied to 2-(imidazo[1,2-a]pyridine-2-yl)phenol (154, Scheme 65) and 2-(1-arylvinyl)phenol derivatives (82, Scheme 66) [144]. Very recently Zhi reported a transition-metal-free carboxylation of C(sp 2 )-H bond with CO 2 followed by a lactonization reaction applied to 2-(imidazo[1,2-a]pyridine-2-yl)phenol (154, Scheme 65) and 2-(1-arylvinyl)phenol derivatives (82, Scheme 66) [144]. For reaction shown in Scheme 65 substrates bearing electron-donating and electro-withdrawing group substituents both at the phenoxy-(R 1 ) and pyridine-(R 2 )-moieties were functionalized in good to excellent yield (17 examples, 56-96% yields).…”
Section: Base-promoted Carboxylation Of Aromatic and Heteroaromatic Cmentioning
confidence: 99%